Dithiophene‐Fused Oxadiborepins and Azadiborepins: A New Class of Highly Fluorescent Heteroaromatics. Issue 17 (17th March 2021) - Crumbach, Merian; Bachmann, Jonas; Fritze, Lars; Helbig, Andreas; Krummenacher, Ivo; Braunschweig, Holger; Helten, Holger
Abstract: Access to dithiophene‐fused oxadiborepins and the first azadiborepins attained via a modular synthesis route are presented. The new compounds emit intense blue light, some of which demonstrate fluorescence quantum yields close to unity. Cyclic voltammetry (CV) revealed electrochemically reversible one‐electron reduction processes. The weak aromatic character of the novel 1, 2, 7‐azadiborepin ring is demonstrated with in‐depth theoretical investigations using nucleus‐independent chemical shift (NICS) scans and anisotropy of the induced current density (ACID) calculations. Abstract : Dithienooxa‐ and ‐azadiborepins are accessible in a modular way from a common precursor. These BNB‐doped polycyclic aromatic hydrocarbons (PAHs) are highly efficient blue‐light emitters with quantum yields up to 96 %. In‐depth theoretical studies reveal that the previously unknown azadiborepin ring system is weakly aromatic.